ARAH POLITIK HUKUM OTONOMI DAERAH (Sebuah Tawaran tentang Model Hukum Humanist Partisipatoris dalam Penyelenggaraan Pemerintahan Daerah yang Otonom) - Zudan Arif Fakrulloh (Perspektif, 2004)
Legal Development is one of the most difficult problems in Indonesia. Two sources of these problems are the pluralism on the social structure and centralistic on making regulation by the government. The “centralistic regulation" is made in universal type and substance. It means, the government pushes and enforces "the same regulation" to the plural society. This "top down system " is not sufficient to empower the society in Indonesia. We must change and shift legal paradigm from “Technocratic Structural " to “Humanize Participators”.